The Function of International Law in Realizing a Just and Peaceful World Order - Muhammad Fikri Aljundi; Mabruri Andatu; Ahmad Noor Rizal; Dziedan Alfathir; Nasywa Salma Saidah; Rifa Rihhadatul Aisya (JUSTICES: Journal of Law, 2025)
As global interdependence continues to grow, international law has become a central pillar in maintaining legal order, justice, and global stability. It serves not only as a regulatory framework for state conduct but also as a tool for peaceful dispute resolution, the protection of human rights, and the management of cross-border challenges such as transnational crime and climate change. This study explores the primary functions of international law in fostering a fair and peaceful world order, while also addressing the practical challenges that arise in its domestic implementation particularly those related to sovereignty conflicts and variations in national legal systems. Employing a descriptive qualitative method through literature analysis, this research reveals that the success of international law depends significantly on state commitment, the alignment of national laws with international norms, and the engagement of civil society and global institutions. The findings aim to enrich both academic understanding and policy development in the field of international law, reinforcing its role as a strategic instrument in shaping a more just, cooperative, and sustainable global legal framework.